The Impact of COVID-19 Pandemic on Sustainable Development Goals (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The COVID-19 pandemic caused a substantial disturbance to societies’ lives and livelihoods, causing us to reevaluate the whole common existence of humans worldwide. Additionally, the novel coronavirus has been a critical obstacle to attaining the United Nations Sustainable Development Goals (SDGs) embraced in September 2015 and set to be reached by 2030. The pandemic has drastically heightened overall job loss and severely lowered employees’ wages. Moreover, the crisis raised persistent gender disparities in workforce participation rates since there was a greater expectation placed on women than men to abandon their jobs to care for their families. Even though the authorities of high-income nations loaned greatly in response to the disease, low-income developing states had limited borrowing ability due to their lesser market creditworthiness. Unfortunately, administrations throughout the world are on the edge of greater debt than at any time in recent memory, outstripping even World War II. The imposed lockdowns drastically lowered human activities, thus causing a transient drop in greenhouse gas discharges, but as the world recovers from the disease, emissions are expected to soar. Henceforward, sustainable and resilient strategies are vital for a healthy and green restoration from the COVID-19 pandemic and the SDGs are essential to this process. Given this background, this speical issue comprises 11 papers published in the Special Issue (SI) entitled “The Impact of the COVID-19 Pandemic on Sustainable Development Goals”, and the aim of this SI was to generally focus on the broad implications of COVID-19 for SDG achievement.